Having a Regular Primary Care Provider Is Associated With Improved Markers of Well-Being Among Children With Attention-Deficit Hyperactivity Disorder. (August 2018) - Rubinstein, Max; Ruest, Stephanie; Amanullah, Siraj; Gjelsvik, Annie
We examined the association between having a regular primary care physician (PCP) and measures of flourishing and academic success in children with attention-deficit hyperactivity disorder (ADHD). We performed a cross-sectional study using data from the 2011-2012 National Survey of Children's Health. Children aged 6 to 17 years with a diagnosis of ADHD were included in the study (n = 8173). The exposure was whether the guardian identified a regular PCP for their child. The outcomes were parental-reported measures of child well-being and academic performance. Among the study population, 8.9% reported no regular PCP. These children were found to be significantly less likely to finish assigned tasks (adjusted odds ratio [OR] = 0.52, 95% confidence interval [CI] = 0.35-0.79), care about school (adjusted OR = 0.62, 95% CI = 0.38-0.92), and finish homework (adjusted OR = 0.58, 95% CI = 0.36-0.88). There were no differences in other examined outcomes. Enhancing longitudinal care for this population may optimize their academic performance.